Undergraduates’ experience and satisfaction of massive open online course in Malaysia - Mohd Nizam Attan; Aizathul Hani Abd Hamid; Muhaymin Hakim Abdullah; Marzudi Md Yunus; Akhmad Mansur (International Journal of Evaluation and Research in Education (IJERE), 2024)
While massive open online course (MOOC) is gaining popularity, studies have shown how negative user experience of the learning platform can lead to issues related to poor learning performance. OpenLearning, as the official national coordinated MOOCs program for higher education institutions in Malaysia, is still considerably gaining momentum in this country, thus much can still be observed in the usability aspect of this platform from the student’s perspective. This study aimed to evaluate the aspects of user experience and learning satisfaction of MOOC OpenLearning involving undergraduate students in a public university in Malaysia. Data were gathered through the online survey method which adapted questions from the user experience questionnaire (UEQ) and the usefulness, satisfaction, and ease of use (USE) questionnaire. Descriptive analyses revealed moderate positive levels of user experience and learning satisfaction towards MOOC OpenLearning among the respondents. Furthermore, there was a significant positive correlation between both factors, suggesting the importance of considering user experience as the key factor in enhancing students’ satisfaction with MOOC. Recommendations arising from the students’ perceptions and concerns on the usability aspect contribute towards developing strategic guidelines for enhancing students’ learning experiences, especially during circumstances that necessitate effective online learning strategies.